A first order finite similitude approach to scaled aseismic structures. (15th March 2021) - Davey, K.; Darvizeh, R.; Atar, M.
Highlights: A new testing approach for scaled aseismic structural experiments. The theory of finite similitude extended to cater for two structural experiments at distinct scales. The breaking of similarity limitations imposed by dimensional analysis on structures. The application of the new theory to practical structural test cases. Abstract: For many decades the designs of earthquake-resistant (aseismic) structures have been influenced by scaled experiments, underpinned by the theory of dimensional analysis. Although scaled experiments still play an important role, they are recognised to suffer shortcomings, which are particularly severe when scaling ratios are pronounced. The issue is one of scale effects and the inability of dimensional analysis to offer any solution in their presence. This paper is concerned with a new theory for the analysis of aseismic structures that is founded on the metaphysical concept of space scaling, where beams, substructures or buildings etc. are contracted through the mechanism of space contraction. Although space contraction is evidently practically impossible the theory describes the effects of such a process on the underpinning governing mechanics involved. Unlike dimensional analysis the approach which is termed finite similitude embraces scale effects and accounts for them by linking experiments at more than one scale. It is demonstrated in this work how it is possible to reconstruct full-scale behaviour by means of two scaled experiments of a selected beam, column and multi-storey structure when subjected to dynamic loading conditions.